Assessment of hepatic fibrosis with superb microvascular imaging in hepatitis C virus‐associated chronic liver diseases. Issue 6 (15th August 2016) - Koyama, Nobuko; Hata, Jiro; Sato, Tokeshi; Tomiyama, Yasuyuki; Hino, Keisuke
Abstract : Aim: Superb microvascular imaging (SMI) is an ultrasound Doppler technique using a unique algorithm that allows visualization of minute vessels with slow velocity and minimal motion artifacts. The aim of this preliminary study was to investigate whether SMI could predict liver fibrosis by visualizing the vessels present in the vicinity of the liver surface because the morphology of the peripheral hepatic vasculature is affected by the progression of liver fibrosis. Methods: We recruited 29 patients with biopsy‐proven chronic hepatitis C or liver cirrhosis C, and 36 patients without liver disease as controls. Using an Aplio 500 ultrasound system with a 7‐MHz or 12‐MHz linear probe, we assessed the vascular shapes and the bifurcation angles of five randomly selected vessels in the vicinity of the liver surface. The vascular shape was scored based on the number of winding and/or irregular vessels. Results: The mean vascular score and the mean bifurcation angle were significantly greater in patients with advanced liver fibrosis (3.5 ± 1.1 and 90.5 ± 14.3) than in those with mild‐to‐moderate liver fibrosis (1.3 ± 1.4 and 68.0 ± 16.1) and controls (0.6 ± 0.7 and 62.2 ± 10.5). The area under the receiver–operating curve of the vascular score and the bifurcation angle were 0.88 with 76.5% sensitivity and 83.3% specificity, and 0.87 with 94.1% sensitivity and 75.0% specificity, respectively. Conclusion: The present results indicate that SMI potentially predicts the extent of liver fibrosis by detecting small vessels present in the vicinity of the liver surface.